The effectiveness of the special physical training program for future officers of higher education institutions in sectional classes in military-applied heptathlon - Moskalenko , Nataliya; Kuryshko , Yevhen (Sportyvnyi Visnyk Prydniprovia, 2026)
Introduction. One of the directions for implementing state policy in the field of physical education of youth and their preparation for the defense of the Native country is the process of physical education in higher military educational institutions. Special physical training is an important component of the training system for servicemen of the Armed Forces of Ukraine. The results of comprehensive theoretical and empirical studies by Ukrainian scientists indicate the necessity of introducing military-applied sports into the system of training youth for service in the Armed Forces of Ukraine, which is also confirmed by the experience of NATO member states that actively implement them in the process of physical training of servicemen in order to achieve maximum approximation to military-professional activity. In our opinion, researchers have overlooked military-applied heptathlon, a sport that is maximally close to military-professional activity, the use of which in the process of sports and mass work is capable of forming professionally necessary military-applied skills and abilities of future officers. The purpose of the study is to determine the effectiveness of a program for improving the special physical training of future officers by means of military-applied heptathlon in sectional classes within the process of sports and mass work of higher military educational institutions to perform tasks related to service activities. Material and methods of the study. The research methods included general scientific, sociological, pedagogical, anthropometric, medical-biological and statistical methods. Results. In order to improve the special physical training of future officers, we developed a step-by-step program of military-applied heptathlon for conducting educational and training sessions during sports and mass work hours for cadets of higher military educational institutions, which included the goal, objectives, conditions of implementation: pedagogical ((implemented through the following components: theoretical, methodological, practical, diagnostic and results-oriented), organizational, psychological, scientific principles of construction (applicability, systematicity, dynamism, consistency, optimality, unity, cyclicality). In the course of the study, its effectiveness was determined. Conclusions. The effectiveness of implementing the author’s program for improving special physical training by means of military-applied heptathlon is confirmed by statistically significant better (p ≤ 0.05–0.01) results in performing special physical exercises. After the experiment, the express assessment of the somatic health level of cadets in the experimental group improved to an average level, unlike representatives of the control group. A reliable (p < 0.05) improvement in the functional change index of the experimental group was also observed, indicating an increase in the adaptive capabilities of future officers who participated in the author’s program.